Resort Hotel Di Kawasan Wisata Pantai Teluk Bogam Pangkalan Bun Dengan Arsitektur Dayak Kontemporer - IBRAHIM, IBRAHIM, Dr. Ir. Qomarun, MM, Ir. Samsudin Raidi, M.sc (2016)
Tourism is a wide range of tourist activities and support berbgai facilities and services provided by the public, employers, government, and local government (Republic Act NO. 10 of 2009 on Tourism). Growing tourism business in the State of Indonesia has various particular purpose which can boost economic growth and improve the welfare of various walks of life. Various natural resources are in this archipelago khusu be an attraction for tourists, both domestic or overseas for vacation and leisure time release. Especially Pangkalan Bun, Central Kalimantan is one of the tourist destinations that attract tourists. Natural and cultural diversity scattered across this area into a tourist attraction. In addition to cultural tourism, which is generally well known, too many natural attractions that are there in the town of Pangkalan Bun as captive orangutans travel namely Tanjung Puting National Park and beach tourism one of them is Bogam Gulf Coast Tourism Region. Sustainability and the wealth of the surrounding natural conditions are expected to remain intact in the presence Beach Resort Hotel as suggestions accommodation for tourists who vacation / visit. Aside from being a means of accommodation Beach Resort Hotel is also preserving the local architecture Houses of Traditional Dayak Longhouse is a house with modern architectural styles unite Contemporary nantinyaakan memebrikan distinctive character.